Robust DMPC for Power System Load Frequency Control with State-Error - Liu, Xiangjie; Zhang, Yi; Qu, Bin (Mobile networks and applications, 2017)
Reliable load frequency control (LFC) is crucial to the operation and design of large-scale power system. However, the huge system is always subject to the running uncertainties and external disturbances. Considering the LFC problem in an interconnected power system with four areas, this paper presents a robust distributed model predictive control (RDMPC) based on linear matrix inequalities(LMIs). The proposed algorithm works out problems of local convex constrained optimizations on LFC by minimizing an attractive range for robustness using a time-varying state-feedback controller in each control area. The scheme incorporates the two critical nonlinear constraints, the generation rate constraint (GRC) and the valve limitation, into convex constrained optimization using LMIs even if the state information of the power system may suffer unexpected lose because of the sensor’s fault. Furthermore, the algorithm explores the use of an expanded group of adjustable parameters in LMIs to transform an upper bound into an attractive range for shunning conservativeness. Good performance and robustness on load frequency uncertainties and its error state are obtained in the interconnected power system.